2009
DOI: 10.1590/s0004-27492009000600018
|View full text |Cite
|
Sign up to set email alerts
|

Roturas retinianas em retinocoroidite por toxoplasmose: série de casos

Abstract: This study is a retrospective case series aiming to evaluate the relation between toxoplasmic retinochoroiditis scars and the occurrence of retinal tears. Ten patients with retinal tear and toxoplasmic retinochoroiditis examined at the School of Medicine of Ribeirão Preto Clinics Hospital, between January 2007 and April 2008, were included. Fisher test and qui-square test with significance level of p<0.05 were used. Eight cases (80%) had retinal detachment. Twelve tears were found and localized mostly in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“… 8 . There are four other case reports in the literature describing RRD associated with toxoplasma chorioretinitis 9 , 10 , 11 , 12 , 13 . Only one study, by Frou et al, had giant retinal tear RRDs documented in their case series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 . There are four other case reports in the literature describing RRD associated with toxoplasma chorioretinitis 9 , 10 , 11 , 12 , 13 . Only one study, by Frou et al, had giant retinal tear RRDs documented in their case series.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, visual outcomes after retinal detachment surgery are poor and re-detachment rates are high. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 . While receiving oral therapy for toxoplasmosis, successful surgical management of a giant retinal tear and retinal detachment was accomplished in this patient with active toxoplasmosis retinochoroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…The same study showed that attacks of active ocular toxoplasmosis preceded retinal tears were characterized by severe intraocular inflammation. The occurrence of retinal tears in patients with uveitis may be related to early posterior vitreous detachment caused by the intraocular inflammatory process [8]. Bodanowitz et al [9] reported that retinal tear in patients with retinitis is associated with toxoplasmosis and that retinal tear is a rare complication of toxoplasmic retinochoroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…Assim como apontado por outros autores a maioria das crianças (n=18; 90%) apresentava lesões de retinocoroidite cicatrizadas já no primeiro exame e apenas duas delas apresentavam doença ativa e descolamento da retina (9) . Esta é uma complicação grave que já foi registrada com maior prevalência em outros estudos (16,17) . Para crianças com toxoplasmose congênita as alterações neurológicas podem implicar em déficits cognitivos e atraso do desenvolvimento psicomotor.…”
Section: Discussionunclassified